2022
DOI: 10.1017/qpb.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genomic insights into cyanobacterial symbioses in plants

Abstract: Photosynthesis, the ability to fix atmospheric carbon dioxide, was acquired by eukaryotes through symbiosis: the plastids of plants and algae resulted from a cyanobacterial symbiosis that commenced more than 1.5 billion years ago and has chartered a unique evolutionary path. This resulted in the evolutionary origin of plants and algae. Some extant land plants have recruited additional biochemical aid from symbiotic cyanobacteria; these plants associate with filamentous cyanobacteria that fix atmospheric nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 134 publications
3
20
0
Order By: Relevance
“…Other COG categories with a high proportion of unique genes were those dedicated to intracellular trafficking, motility and signal transduction mechanisms (). The importance of these mechanisms in cyanobiont symbiosis has been previously reported [25, 27, 28]. Interestingly, genomes from clade SYMB-1 contained a lower fraction of unique genes from these categories than those from SYMB-2 and 3 (), in line with what was observed in the pangenomic analysis, namely that based on composition, genomes from SYMB-1 are closer to FL-II than SYMB-2 and 3 are to their sister clade FL-XI ().…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Other COG categories with a high proportion of unique genes were those dedicated to intracellular trafficking, motility and signal transduction mechanisms (). The importance of these mechanisms in cyanobiont symbiosis has been previously reported [25, 27, 28]. Interestingly, genomes from clade SYMB-1 contained a lower fraction of unique genes from these categories than those from SYMB-2 and 3 (), in line with what was observed in the pangenomic analysis, namely that based on composition, genomes from SYMB-1 are closer to FL-II than SYMB-2 and 3 are to their sister clade FL-XI ().…”
Section: Discussionsupporting
confidence: 83%
“…An alpha value of <1 from the power law was obtained for the entire Nostocales super-clade, indicating an open pangenome [72] consistent with the multiple lifestyles characteristic of these species [73]. Similarly, the symbiotic clades exhibited an open pangenome, which is consistent with a facultative symbiotic lifestyle [28, 74] ().…”
Section: Resultsmentioning
confidence: 93%
“…Hornworts host the cyanobacteria in mucilage cavities that can be accessed through ventral mucilage clefts, which superficially resemble stomata ( Renzaglia et al., 2000 ; Villarreal A and Renzaglia, 2006 ). An exception is L. dussii that hosts cyanobacteria in canals that branch and form an integrated network within the thallus ( de Vries and de Vries ; Meeks, 2003 ).…”
Section: The Unique Biology Of Hornwortsmentioning
confidence: 99%
“…Data from the Arctic Ocean revealed that approximately 50 mya, an abundance of Azolla characterized an 800 000‐year interval called the “ Azolla event,” which possibly had a role in global cooling by sequestering atmospheric carbon dioxide (Brinkhuis et al., 2006; Speelman et al., 2009). Azolla is further remarkable due to its obligate symbiosis with the N‐fixing cyanobacterium Nostoc azollae in specialized leaf cavities (de Vries et al., 2018; de Vries & de Vries, 2022; Li et al., 2018). Ceratopteris richaridii is also adapted to water and is known as the genetically tractable fern model organism (“C‐Fern”; Plackett et al., 2015) and as a teaching tool in biology (Renzaglia & Warne, 1995).…”
Section: Introductionmentioning
confidence: 99%